PENGARUH RASIO PROFITABILITAS TERHADAP HARGA SAHAM - Septiani, Muthia Zahra; Suhono, Suhono (Jurnal USAHA, 2025)
The study aims to analyze the extent to which ROA and NPM will affect the stock prices of insurance companies on the Indonesia Stock Exchange during the 2019-2023 period. Sampling using the purposive sampling technique method. The population is 18 companies, and there are 7 companies whose sample criteria are included for 5 periods. Secondary data is obtained through annual financial reports and historical stock price data. Sample testing is supported by SPSS software version 22. The results of the study show that ROA has an effect on stock prices, while NPM does not show any effect on stock prices. However, it simultaneously has an impact on the stock prices of insurance sub-sector companies on their stock prices listed on the IDX during that time period.